Current antitrust issues in U.S. Federal Eforcement - Steptoe, Mary Lou (Revista do IBRAC, 2025)
It is a very great pleasure to address this noted body of international antitrust experts. In my time on the podium I will address three topics -- three areas of antitrust law where the U.S. antitrust agencies, the Federal Trade Commission ("FTC") and the Antitrust Division of the Department of Justice ("DOJ"), are breaking new ground. My first topic will be the agencies' resurgence of enforcement activity in the area of vertical price fixing. Then I will turn to the agencies' concern with a new type of merger; and finally I will describe a new type of review protocol, the "Quick Look", which is helping the agencies manage their resources in a time of increased caseload and shrinking budget.